2021
DOI: 10.1111/jcmm.16261
|View full text |Cite
|
Sign up to set email alerts
|

Recepteur d'origine nantais contributes to the development of endometriosis via promoting epithelial‐mesenchymal transition of a endometrial epithelial cells

Abstract: Endometriosis is a benign, chronic inflammatory disease that commonly occurs in reproductive‐aged women. Epithelial ‐ mesenchymal transition (EMT) of endometrial epithelial cells plays an important role in the development of endometriosis. Recepteur d'origine nantais (RON), a receptor tyrosine kinase, has been reported to promote EMT and progression in tumours. However, whether and how RON mediates the EMT and endometriosis development is not known. Here, we found that RON activation cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Common transcription factors include ZEB family, Snail family, or Twist family [ 34 , 35 ]. In HEC-1B cells, we found that the transcription factor affected by RON was ZEB2, which was consistent with previous results obtained using MSP to stimulate endometrial epithelial cells with MSP (the agonist of RON) [ 36 ]. Increased expression of ZEB2 resulted in decreased expression of E-cadherin.…”
Section: Discussionsupporting
confidence: 92%
“…Common transcription factors include ZEB family, Snail family, or Twist family [ 34 , 35 ]. In HEC-1B cells, we found that the transcription factor affected by RON was ZEB2, which was consistent with previous results obtained using MSP to stimulate endometrial epithelial cells with MSP (the agonist of RON) [ 36 ]. Increased expression of ZEB2 resulted in decreased expression of E-cadherin.…”
Section: Discussionsupporting
confidence: 92%
“…Chen et al revealed a significant decrease in E-cadherin expression and a significant increase in C-X-C motif chemokine 12 in the endometrial tissue of EM patients (Chen et al, 2020). Another finding presented by Yu et al (2021) showed strong staining of N-cadherin and E-cadherin in endometriotic lesions and control endometria, respectively. These observations show that EMT participates in the development of EM, and is a workable indicator in tracing the aetiology of the disease.…”
Section: Discussionmentioning
confidence: 88%
“…Chen et al revealed a significant decrease in E-cadherin expression and a significant increase in C-X-C motif chemokine 12 in the endometrial tissue of EM patients ( Chen et al, 2020 ). Another finding presented by Yu et al (2021) showed strong staining of N-cadherin and E-cadherin in endometriotic lesions and control endometria, respectively. These observations show that EMT participates in the development of EM, and is a workable indicator in tracing the aetiology of the disease.…”
Section: Introductionmentioning
confidence: 88%